2019
DOI: 10.1038/s41598-019-51673-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of obesity-related cardiometabolic and renal biomarkers in human plasma and serum

Abstract: The search for biomarkers associated with obesity-related diseases is ongoing, but it is not clear whether plasma and serum can be used interchangeably in this process. Here we used high-throughput screening to analyze 358 proteins and 76 lipids, selected because of their relevance to obesity-associated diseases, in plasma and serum from age- and sex-matched lean and obese humans. Most of the proteins/lipids had similar concentrations in plasma and serum, but a subset showed significant differences. Notably, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…In line with our results, both proteins are reduced with increasing obesity 24 and an US‐American cohort study using single biomarkers measured with radioimmunoassays showed that higher total per cent fat and higher visceral fat were associated with lower IGFBP1 and IGFBP2 25 . In a Swedish PEA‐based‐proteomics study, IGFBP1 was inversely associated with BMI‐defined obesity 15 and by using aptamer methodology, IGFBP1 was inversely associated with fat mass (kg) 16 . Concerning muscle mass, IGFBP1 was inversely associated with DXA‐measured low relative muscle mass in a Swedish cohort of elderly women 26 and IGFBP2 was inversely associated with DXA‐measured total muscle mass in an US‐American study 27 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In line with our results, both proteins are reduced with increasing obesity 24 and an US‐American cohort study using single biomarkers measured with radioimmunoassays showed that higher total per cent fat and higher visceral fat were associated with lower IGFBP1 and IGFBP2 25 . In a Swedish PEA‐based‐proteomics study, IGFBP1 was inversely associated with BMI‐defined obesity 15 and by using aptamer methodology, IGFBP1 was inversely associated with fat mass (kg) 16 . Concerning muscle mass, IGFBP1 was inversely associated with DXA‐measured low relative muscle mass in a Swedish cohort of elderly women 26 and IGFBP2 was inversely associated with DXA‐measured total muscle mass in an US‐American study 27 .…”
Section: Discussionsupporting
confidence: 90%
“…FABP4, ADM, PRSS27, and PON3 were only associated with the continuous and categorical parameters of BFMI. In a previous PEA‐proteomics study, ADM and FABP4 were positively associated with BMI‐defined obesity 15 . An increase in FABP4 was also associated with an increase in BMI and WHR over 10 years 14 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Bridge et al showed that HCV genotype 3 patients had lower and HCV genotype 1 patients had higher plasma PCSK9 levels compared to uninfected controls [ 24 ]. It must be noted that plasma and serum PCSK9 levels do not correlate, and it is debatable whether studies using different biofluids can be compared [ 34 ]. In HIV-infected patients, coinfection with HCV increased plasma PCSK9 levels [ 35 ].…”
Section: Discussionmentioning
confidence: 99%